The Implication of the 2011 General Elections on Democracy and Good Governance in Nigeria. - Nwagboso, Chris Iwejuo; Duke, Otu (Advances in Social Sciences Research Journal, 2015)
This paper discusses the implication of the 2011 general elections on democracy and good governance in Nigeria using descriptive method as a mode of analysis. The paper attempts a critical discourse of how the abysmal failures of the stakeholders in the 2011 general elections in Nigeria like the INEC, political parties, security agents and the media, to administer credible elections would affect democracy and good governance in Nigeria. Thus, secondary data such as library research, newspaper articles and internet retrievals were used in this investigation. The results of the analyses revealed that the 2011 general election were flawed, due to compromise among the major stakeholders. The paper further argues that although the conduct of the 2011 general elections was comparatively better than the previous elections conducted in Nigeria such as 1999, 2003, and 2007, the election fraud and rigging in the 2011 general elections were mostly prevalent during the Governorship and State Assembly elections, particularly in the South-East and South-South geo-political zones of Nigeria. Therefore, the paper recommends among others, the adoption of electronic voting system, credible party primaries by political parties by the INEC as critical steps to restore sanity in Nigeria’s electoral process.